Marketing mix factors influencing the service decision process Government Savings Bank Business Loan in Ubon Ratchathani Province - Krugnsri, Jularat (Journal of Human and Society, Sisaket Rajabhat University, 2022)
This research has the objective for (1) to study the marketing mix factors that influence the decision making process for using the Government Savings Bank business loan service. in Ubon Ratchathani Province. 2) to compare the mix factors marketing that influences the decision making process for using Government Savings Bank business loans in the province of Ubon Ratchathani classified by personal factors, the sample group used in the research was using a random sampling method from customers who used to use the service with The Government Savings Bank in Ubon Ratchathani Province, 23 branches, received a total sample of 302 people, which proportional terrain The tools that were used in the research are questionnaire and statistic to analyze the data are, percentage, mean, deviation, Standard Multiple Regression Analysis t-Test and F-Test The results of the research found out that: 1. The product/service factors Interest rates and fees physical appearance and marketing promotion affects the decision making process for the Government Savings Bank business loan in Ubon Ratchathani Province with statistical significance at the 0.01 level and factors of location and service channels affects the decision making process for the Government Savings Bank business loan in Ubon Ratchathani Province statistically significant at the 0.05 level. 2. When comparing the marketing mix factors that influence the decision making process Government Savings Bank Business Loan in Ubon Ratchathani Province, classify by personal factor found that the users with sex, age, marital status education level period of business and different average monthly income, there are no different opinions. The product/service location and service channels Interest rates and fees marketing promotion and physical characteristics, different business types had statistically different opinions on physical characteristics at the 0.05 level.